Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1186/1475-2875-6-146
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of artemisinin-based antimalarial in the treatment of uncomplicated malaria in children in southern Tanzania

Abstract: Background: Tanzania switched the antimalarial first line to sulphadoxine-pyrimethamine (SP) in 2001 from ineffective chloroquine (CQ). By 2003 higher levels of SP resistance were recorded, prompting an urgent need for replacing the first line drug with ACT, as currently recommended by the World Health Organization. Despite this recommendation country-specific evidence-based data to support efficacy and safety profile of ACT is still limited. A study on the efficacy and safety of artesunate plus amodiaquine (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
44
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 15 publications
(14 reference statements)
17
44
1
Order By: Relevance
“…Overall, the study showed a high efficacy of the two forms of ACTs in Nigerian children; the PCR-adjusted cure rate on day 28 was 100% in both treatment groups. These results are in agreement with earlier studies in Nigeria that have shown both combinations to be safe and well tolerated [7,8,17] and are also consistent with the high cure rates that have been reported for ACT in other malaria-endemic areas of Africa [18][19][20]. Artemisinin and related endo-peroxide antimalarials act rapidly by clearing P. falciparum in the blood, thereby providing prompt therapy for severe infections [21].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Overall, the study showed a high efficacy of the two forms of ACTs in Nigerian children; the PCR-adjusted cure rate on day 28 was 100% in both treatment groups. These results are in agreement with earlier studies in Nigeria that have shown both combinations to be safe and well tolerated [7,8,17] and are also consistent with the high cure rates that have been reported for ACT in other malaria-endemic areas of Africa [18][19][20]. Artemisinin and related endo-peroxide antimalarials act rapidly by clearing P. falciparum in the blood, thereby providing prompt therapy for severe infections [21].…”
Section: Discussionsupporting
confidence: 91%
“…Some studies have reported a marginally higher day 28 PCR-corrected cure rate for artemether-lumefantrine over artesunate plus amodiaquine as opposed to others. Generally, studies from eastern Africa [18,24] seem to suggest that artemether-lumefantrine has more clinical benefits than artesunate plus amodiaquine, while studies from western Africa [17,20] show that artesunate plus amodiaquine tend to have marginally better efficacy rates over artemether-lumefantrine. The reason for this The figure shows the percentage reduction of parasitaemia from the recruitment day (day 0) over the follow-up period of 28 days according to the per-protocol analysis observation needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] In contrast, results from Central and East Africa show higher efficacy of AL than ASAQ, especially a higher potency in preventing reinfections. 14,40 In the present study, both treatments were equivalent regarding parasite and fever clearance rates and gametocyte carriage. As already described, 29 ACTs triggered a rapid asexual parasite clearance in the present cohort.…”
Section: Discussionmentioning
confidence: 52%
“…In this study, we analyzed and compared malaria patients who were enrolled in Cambodia and Tanzania. Artemether-lumefantrine (AL) has been the first-line treatment for uncomplicated malaria since the end of 2006 and displays good efficacy in Tanzania (18). In Cambodia, however, its efficacy since 2002 has been reported in all but one study to be considerably and consistently lower (19,20,21).…”
mentioning
confidence: 99%